(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Elevated serum Ferritin level is associated with the increased risk of ischemic stroke, stroke severity, the progression of stroke status, but functional outcome is unsettled.Objective: To determine the association between admission serum ferritin level and 90 days outcome in patients with acute ischemic stroke. Methodology: This hospital-based observational study was conducted in the Department of Neurology of Dhaka Medical College Hospital from July 2018 to June 2019. Total 95patients, age e”18 years with acute ischemic stroke were selected according to the inclusion & exclusion criteria. Serum ferritin level was measured within 48 hours of stroke and the functional outcome of these patients was assessed at day 90 with the modified Rankin Scale(mRS). Results: The mean age was 57.63 ±11.30 years with a range from 25-85 years.The mean Ferritin level was 131.50 ±51.49 found in mRS1,151.61 ±40.16 in mRS 2,177.15 ±72.46 in mRS3, 324.71±107.05 in mRS 4,426.50 ±2.12 in mRS 5, and 429.16 ±84.13 in mRS 6. The above findings indicate that the mRS score increase with the mean ferritin level. It is statistically significant (p-value <0.05). On the Receiver operating characteristic (ROC) curve, ferritin level had an area under curve 0.946 and gave a cut off value 388 with 71.4% sensitivity and 89.3% specificity. The binary logistic regression model showed that elevated serum Ferritin had a positive impact on pooroutcome after adjusting all independent variables. Conclusion: Elevated serum Ferritin level on admission was significantly associated with 90 days poor outcome in patients with acute ischemic stroke.